Long-term clinical outcomes of keratoplasty using gamma-irradiated corneal lenticules. Issue 1 (10th November 2019) - Mathews, Priya M; Fogla, Rajesh; Samayoa, Erik; VanCourt, Shanna; Akpek, Esen K
Abstract : Objective: To report long-term clinical outcomes of gamma-irradiated corneal lenticules in partial and full-thickness keratoplasty. Methods and Analysis: This multicentre, retrospective case series includes 23 patients who underwent surgery at three centres (India, Guatemala, and USA) between May 2009 and March 2018. The main outcome measures were epithelialization and retention for therapeutic keratoplasty and best spectacle-corrected visual acuity (BSCVA) for optical keratoplasty. Results: Patients were categorised according to primary aetiology requiring corneal transplantation: non-inflammatory conditions, infectious keratitis and sterile keratolysis. Nine patients with non-inflammatory conditions underwent anterior lamellar keratoplasty (n=7) and Boston type 1 keratoprosthesis (n=2). All nine grafts remained intact and epithelialized during follow-up (median 24 months). In the seven patients who underwent anterior keratoplasty, the graft stayed optically clear during follow-up (median 12 months), with BSCVA between 20/20 and 20/40 in all but one patient who developed cataract. Nine patients with severe infectious keratitis had emergency patch grafting. Six of those grafts epithelialized and remained intact over a median of 30 months, providing tectonic support until optical keratoplasty with fresh tissue could be performed. Three grafts had recurrent infectious keratitis 1–3 months postoperatively, two of which underwent tectonic keratoplasty with fresh tissue which also eventually became infected during follow-up. In five additional patients with sterile keratolysis who underwent lamellar patch graft, two grafts remained intact during follow-up (median 36 months). Two patients had recurrent corneal melt within 1 month, and both had subsequent corneal surgery with fresh tissue which also failed. There were no donor-related complications. Conclusion: Gamma-irradiated sterile corneal stromal lenticules can be considered as a viable alternative to fresh tissue in various clinical settings.